Analyzing Hydroponic Rack System For Apartment House - Talib, Mohd Hafiz; Abd Rahman, Khairul Aidil Azlin; Dollah, Shahrizal (2016)

(untitled)
The objective of this study is to identify hydroponic system for those who are living in condo and apartment in an urban area. Livings in condo and apartment have limited space to do farming activity. Furthermore the management of condo does not allow people to farming in the corridor area. Space has always been the big problem for those who live in urban areas. Other than that design of the existing hydroponic system is not suitable for the current needs. The aim of this study is, to help people so that they can farm in a small area and have limited space in the urban area; it’s also to create awareness how important of planting crop in the living area. Meeting the farmer around Serdang and Terengganu. The surveys in several areas, among them are the MAHA exhibition. Has garnered some agricultural entrepreneurs in Malaysia and abroad. The survey was also done at the condo housing and apartment area around Kuala Lumpur.